Identification of four species of Clupeiformes (Actinopterygii) through analysis of mitochondrial DNA sequences in fishing exploitation areas of the Gulf of Nicoya, Costa Rica - Sancho-Blanco, Carolina (2021)
Sardines, together with anchovies, constitute one of the most important groups in the fishery of the Gulf of Nicoya. They are consumed by large fish and seabirds; therefore, they not only suffer from fishing exploitation but also have high rates of natural mortality. Due to their commercial and ecological importance, it is necessary to have a reliable taxonomic identification of these species, mainly for the preparation of fisheries studies. Previously, the identification of fish species was based only on external morphological characteristics; however, this is not always possible due to their morphological similarity, but the combined use of morphological and genetic data based on mitochondrial genes can contribute to their accurate recognition. Historically, taxonomic studies have grouped the species O. libertate, O. medirastre and O. bulleri as members of the Opisthonema spp. complex due to their great morphological similarity, while, there are few taxonomic studies  of the family Engraulidae. In the present work, species of the Opisthonema spp. complex and a species of the genus Cetengraulis sp., collected between June-December 2017, were molecularly identified by sequencing mitochondrial genes: COI, Ctyb, and 16S rRNA. The findings of the molecular data analysis confirm the identity and presence of three species of the Opisthonema spp. complex and a species of anchovy, in areas of fishing exploitation in the gulf of Nicoya, Costa Rica, information that facilitates the use and management of these fishing resources in a marine area of ​​commercial importance for the country.